Phase Diagram and Estimation of Flory-Huggins Parameter of Interaction of Silk Fibroin/Sodium Alginate Blends - Lopes, Laise Maia; de Moraes, Mariana Agostini; Beppu, Marisa Masumi (Frontiers in Bioengineering and Biotechnology, 2020)
Silk fibroin (SF) and sodium alginate (SA) are natural polymers used to produce biomaterials. One of the strategies to improve the properties of these products is to prepare blends with them, which are partially miscible. Phase separation is observed, therefore, the thermodynamic analysis of this system is important to predict the final state and composition of this blends. This study explored blends with a different initial composition of SF, SA and water (WA) at 25 ºC and neutral pH. After phase separation, two phases were identified, one rich in SF and other rich in SA. The Flory-Huggins parameters of interaction of polymer-solvent and polymer-polymer were estimated using the extended equation and data of phase equilibrium, their values indicates the partial miscibility of the polymers.